THE INFLUENCE OF BEHAVIORAL LOYALTY AND ATTITUDINAL LOYALTY ON PURCHASE BEHAVIOR - Sondakh, Brainly (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2013)
ABSTRACT Creative, innovative, work effectively, and efficiently are demand for the company to show its competitive advantage in the competitive business world. Every product and service that produced must surely attract the attention of customers so the products or services that produced will become customers' choice to use, and aims to be a loyal. Customer will be loyal if the products or services that provided make them satisfied. The research objectives are to analyze the influence of behavioral loyalty and attitudinal loyalty to purchase behavior of Bentenan Fabric in North Sulawesi. Theories supporting this research are customer loyalty and purchase behavior. The population observed is people that buy and wear Bentenan Fabric of north Sulawesi with sample as many as 100 respondents. Results and conclusions are behavioral loyalty has negative correlation with purchase behavior and attitudinal loyalty is the most influencing variable.Keywords: customer loyalty, purchase behavior